Randomized clinical trial on the effect of coffee on postoperative ileus following elective colectomy - Müller, Sascha A.; Rahbari, Nuh Nabi; Schneider, Frank; Warschkow, René; Simon, Thomas; Frankenberg, Moritz von; Bork, Ulrich; Weitz, Jürgen; Schmied, Bruno; Büchler, Markus W. (The British journal of surgery, 2012)
Background: Postoperative ileus is a common problem after abdominal surgery. It was postulated that coffee intake would decrease postoperative ileus after colectomy. Methods: This was a multicentre parallel open-label randomized trial. Patients with malignant or benign disease undergoing elective open or laparoscopic colectomy were assigned randomly before surgery to receive either coffee or water after the procedure (100 ml three times daily). The primary endpoint was time to first bowel movement; secondary endpoints were time to first flatus, time to tolerance of solid food, length of hospital stay and perioperative morbidity. Results: A total of 80 patients were randomized, 40 to each group. One patient in the water arm was excluded owing to a change in surgical procedure. Patient characteristics were similar in both groups. In intention-to-treat analysis, the time to the first bowel movement was significantly shorter in the coffee arm than in the water arm (mean(s.d.) 60·4(21·3) versus 74·0(21·6) h; P = 0·006). The time to tolerance of solid food (49·2(21·3) versus 55·8(30·0) h; P = 0·276) and time to first flatus (40·6(16·1) versus 46·4(20·1) h; P = 0·214) showed a similar trend, but the differences were not significant. Length of hospital stay (10·8(4·4) versus 11·3(4·5) days; P = 0·497) and morbidity (8 of 40 versus 10 of 39 patients; P = 0·550) were comparable in the two groups. Conclusion: Coffee consumption after colectomy was safe and was associated with a reduced time to first bowel action. Registration number: NCT01079442 (http://www.clinicaltrials.gov). Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.